2017
DOI: 10.1021/acs.iecr.7b00990
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Sensitive Nanomaterials for Cancer Therapeutics and Imaging

Abstract: Many diseases can be characterized by the abnormal activity exhibited by various biomolecules, the targeting of which can provide therapeutic and diagnostic utility. Recent trends in medicine and nanotechnology have prompted the development of protease-sensitive nanomaterials systems for therapeutic, diagnostic, and theranostic applications. These systems can act specifically in response to the target enzyme and its associated disease conditions, thus enabling personalized treatment and improved prognosis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 127 publications
0
39
0
Order By: Relevance
“…However, this phenomenon may not play a role with inhalable delivery, but the localization of therapeutics directly in the lungs does provide a means of passively targeting tumor tissues (Azarmi et al, 2006). More active targeting mechanisms, such a pH-triggered release and enzymatic responsivity, are able to further improve the therapeutic efficacy of these systems (Anderson & Cui, 2017;Danhier, 2016). In regards to lung cancer, active targeting by designing nanomaterials to interact with tumor-specific ligands, such as the epithelial growth factor receptor (EGFR) (Rusch et al, 1997), folate receptor (Nogueira et al, 2015;O'shannessy et al, 2012), and the luteinizing hormone-releasing hormone (LHRH) receptor (Dharap et al, 2005), has been thoroughly studied and proven to enhance antitumor efficacy (Saad et al, 2008).…”
Section: Inhalable Therapeutics For Lung Cancermentioning
confidence: 99%
“…However, this phenomenon may not play a role with inhalable delivery, but the localization of therapeutics directly in the lungs does provide a means of passively targeting tumor tissues (Azarmi et al, 2006). More active targeting mechanisms, such a pH-triggered release and enzymatic responsivity, are able to further improve the therapeutic efficacy of these systems (Anderson & Cui, 2017;Danhier, 2016). In regards to lung cancer, active targeting by designing nanomaterials to interact with tumor-specific ligands, such as the epithelial growth factor receptor (EGFR) (Rusch et al, 1997), folate receptor (Nogueira et al, 2015;O'shannessy et al, 2012), and the luteinizing hormone-releasing hormone (LHRH) receptor (Dharap et al, 2005), has been thoroughly studied and proven to enhance antitumor efficacy (Saad et al, 2008).…”
Section: Inhalable Therapeutics For Lung Cancermentioning
confidence: 99%
“…in close proximity of cancer cells. 2,6,[12][13][14][15][16][17][18][19][20] Several studies suggested a mechanism that involves an initial internalization of the precursor by the cells, followed by intracellular enzymatic transformation and assembly that leads to cellular death. 6,18,21 Most of the described precursors are based on short self-assembling peptides that are functionalized with enzymatic sensitive moieties.…”
Section: Introductionmentioning
confidence: 99%
“…6,18,21 Most of the described precursors are based on short self-assembling peptides that are functionalized with enzymatic sensitive moieties. 11,12,17,[19][20][21] We recently demonstrated the use of a glucose derivative, N-uorenylmethyloxycarbonyl-glucosamine-6-phosphate (FGlcP), as an alternative to peptide-based systems in phosphatase-triggered BSA cancer management. 7 For this system, we did not observe any intracellular assembly but formation of a nanoscale supramolecular network around osteosarcoma cells that overexpress membrane-bound alkaline phosphatase (ALP).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal enzymatic activities are implicated in many human diseases such as cancer and represent a popular target for disease treatment . In particular, the expression and release of matrix metalloproteinases (MMPs) is linked to tumor aggressiveness and metastasis, and has been a subject of heavy interest in the development of enzyme‐responsive biomaterials. For instance, the group of Xu pioneered the use of enzymes as a trigger for self‐assembly into biologically relevant nanomaterials .…”
Section: Introductionmentioning
confidence: 99%